Cited4 is a sex-biased mediator of the antidiabetic glitazone response in adipocyte progenitors - Bayındır-Buchhalter, İrem; Wolff, Gretchen; Lerch, Sarah; Sijmonsma, Tjeerd P.; Schuster, Maximilian; Gronych, Jan; Billeter, Adrian; Babaei, Rohollah; Krunic, Damir; Ruas, Jorge L.; Müller, Beat P.; Lichter, Peter; et al. (EMBO molecular medicine, 2018)
Most antidiabetic drugs treat disease symptoms rather than adipose tissue dysfunction as a key pathogenic cause in the metabolic syndrome and type 2 diabetes. Pharmacological targeting of adipose tissue through the nuclear receptor PPARg, as exemplified by glitazone treatments, mediates efficacious insulin sensitization. However, a better understanding of the context-specific PPARg responses is required for the development of novel approaches with reduced side effects. Here, we identified the transcriptional cofactor Cited4 as a target and mediator of rosiglitazone in human and murine adipocyte progenitor cells, where it promoted specific sets of the rosiglitazone-dependent transcriptional program. In mice, Cited4 was required for the proper induction of thermogenic expression by Rosi specifically in subcutaneous fat. This phenotype had high penetrance in females only and was not evident in beta-adrenergically stimulated browning. Intriguingly, this specific defect was associated with reduced capacity for systemic thermogenesis and compromised insulin sensitization upon therapeutic rosiglitazone treatment in female but not male mice. Our findings on Cited4 function reveal novel unexpected aspects of the pharmacological targeting of PPARg.